Effects of Different Stand Densities on the Composition and Diversity of Soil Microbiota in a Cunninghamia lanceolata Plantation - Zuyuan Xu; Fei Fan; Qinmin Lin; Shengzhou Guo; Shumao Li; Yunpeng Zhang; Zhiyi Feng; Xingxing Wang; Christopher Rensing; Guangqiu Cao; Linkun Wu; Shijiang Cao (Plants)
As sustainable forest management gains increasing attention, comprehending the impact of stand density on soil properties and microbial communities is crucial for optimizing forest ecosystem functions. This study employed high-throughput sequencing in conjunction with soil physicochemical analysis to assess the effects of stand density on soil physicochemical properties and microbial community characteristics in Chinese fir plantations, aiming to elucidate the influence of density regulation on ecosystem services. Our results suggested that changes in soil physicochemical properties and microenvironmental conditions were key drivers of soil microbial diversity. Total carbon (TC), soluble nitrogen (SN), and light fraction organic matter decreased with increasing stand density, while total potassium (TK) and available phosphorus (AP) concentrations increased. The plot with a density of 900 trees ha−1 exhibited the highest bacterial diversity, in contrast to the plot with 1500 trees ha−1, which showed the lowest. The dominant microbial taxa were similar across different stand retention densities, with Acidobacteria, Proteobacteria, and Chloroflexi being the predominant bacterial phyla and Ascomycota and Basidiomycota being the main fungal groups. Significant positive correlations were observed between soil microbial community structures and environmental factors, particularly with respect to soil phosphorus and nitrogen content. The present study demonstrated that reduced stand densities modulated soil nutrient content and enhanced bacterial diversity, thereby contributing to a more complex and stable soil ecosystem structure. These insights provide a scientific foundation for optimizing the management of Chinese fir plantations, thereby supporting the sustainable development of forest ecosystems.